Pharmacotherapy for Hyperglycemia in Noncritically Ill Hospitalized Patients - Mendez, Carlos E. (Diabetes Spectr, 2014)
In Brief Hyperglycemia in the hospital setting affects 38-46% of noncritically ill hospitalized patients. Evidence from observational studies indicates that inpatient hyperglycemia, in patients with and without diabetes, is associated with increased risks of complications and mortality. Substantial evidence indicates that correction of hyperglycemia through insulin administration reduces hospital complications and mortality in critically ill patients, as well as in general medicine and surgery patients. This article provides a review of the evidence on the different therapies available for hyperglycemia management in noncritically ill hospitalized patients.